Yagi-Uda Antennas for Private LTE Band 3 FDD: Simulation, Fabrication, and Measurement - Muhammad Rizko Justiano; Aryanti Aryanti; Mohammad Fadhli (Aviation Electronics, Information Technology, Telecommunications, Electricals, and Controls (AVITEC), 2026)
Private LTE Band 3 Frequency Division Duplex (FDD) systems require dedicated uplink and downlink antennas to improve channel isolation and communication reliability. However, experimentally validated split-frequency Yagi-Uda antennas for Software Defined Radio (SDR)-based base stations remain limited. This study presents the design, simulation, fabrication, and experimental validation of two four-element Yagi-Uda antennas operating at 1.840 GHz for downlink (DL) and 1.750 GHz for uplink (UL). Each antenna consists of one reflector, one driven element, and two directors fabricated from 6 mm diameter aluminum rods. The antenna dimensions were optimized using the Trust Region Framework in CST Studio Suite 2024 to achieve optimal impedance matching. Simulation results produced S11 values of −35.33 dB (DL) and −30.76 dB (UL), VSWR values of 1.035 and 1.059, and forward gains of 9.10 dBi and 8.38 dBi, respectively. Measurements using a NanoVNA over the 1.4–2.1 GHz frequency range yielded S11 values of −18.98 dB (DL) and −26.92 dB (UL), with corresponding VSWR values of 1.253 and 1.094. The measured resonant frequencies closely agreed with the simulation results, with a maximum deviation of only 1 MHz. The novelty of this work lies in the experimental validation of a low-cost, split-frequency, four-element aluminum-rod Yagi-Uda antenna pair that operates without an external impedance-matching network. These results demonstrate the suitability of the proposed antennas for SDR-based Private LTE Band 3 base station applications.